Separação e pré-concentração on-line para especiação de Hg em chorume por FI-CVG AAS - Flores, Éder Lisandro de Moraes (2005)
In Brazil, the urban solid wastes are usually discharged on landfill sites that are percolated by rainwater. This water leaches the wastes producing an effluent that is characterized by high concentration of organic matter, salts, suspended particulates and heavy metals. Mercury is one of the metals that is frequently present in different chemical forms which is an environmental concern. Since some mercury species, mainly Hg2+ (Hginorg) and CH3Hg+ (Hgorg.), are more toxic than others, the Hg speciation in the waste leaching is very important. This analysis may be a difficult task due to low analyte concentration and high matrix complexity. In this work it is proposed a new method for Hg speciation in urban waste leachate by using a flow injection (FI) system for chemical vapor generation (CVG) and detection by atomic absorption spectrometry (AAS). The sample was centrifuged at 15,000 rpm for 10 min for separating the particulates. The supernatant was filtered at 0.45 μm, acidified up to 1 mol L-1 HCl and then passed through a column (l = 10 mm and i.d. = 3 mm) filled with anion exchange resin (Dowex 1-X8, 200-400 mesh) in order to retain only the Hginorg. Just at the column outlet the MeHg, which is not retained by the resin, is converted to volatile MeHgH by reaction with 0.1% (m/v) NaBH4 and the MeHgH is subsequently pre-concentrated by amalgamation on a gold gauze (l = 10 mm and i.d. = 3 mm). Initially, the Hginorg that is retained on the resin is removed by reductive elution with 0.1% (m/v) NaBH4 and 1 mol L-1 HCl and the resultant Hgo is carried by argon to the quartz cell of the AAS spectrometer. In a second step, the MeHgH is thermodesorbed from the Au net by irradiation with a halogen lamp (~500 °C) and the Hgo is also carried by argon to the quartz cell. In this way, is possible the individual detection of the Hg species. The Hg in the solid fraction attained after centrifugation was acid extracted with 6 mol L-1 HCl and microwave irradiation (3 min at 60 W) and then centrifuged once more. The supernatant was separated and submitted to the same procedure described above. With the proposed method it is possible to obtain calibration curves ranging from 50 to 1500 ng L-1 of Hg (as Hg2+ or CH3Hg+). Limits of detection (3s) of 12 ng L-1 of Hg (as Hg 2+) and 9 ng L-1 of Hg (as CH3Hg+) by processing 10 mL of sample were achieved. The recoveries of Hg2+ and CH3Hg+ in the samples spiked with this species were quantitative (97 - 106%) and the relative standard deviation (RSD) was lower than 4% (n = 5).